Three Cases of Severe Placental Abruption as a First Symptom of Preeclampsia. (24th July 2021) - Mikuscheva, Anastasia; Strassding, Finn; MacKenzie, Elliot
Abstract : Placental abruption is often referred to in the literature as a complication of preeclampsia. We report 3 recent cases where the first symptom of preeclampsia was placental abruption. All women were previously healthy and in their first ongoing pregnancy. All had been seen by obstetricians for regular pregnancy checkups. None of the patients had a preexisting diagnosis of preeclampsia. Only one of the patients had risk factors for preeclampsia and occasional hypertension. In all cases, laboratory signs of preeclampsia were abnormal intra- or immediately postpartum. One fetus died in utero, and the other two pregnancies fortunately showed a favourable outcome.